Ewing Sarcoma of the Bone With EWS/FLI1 Translocation After Successful Treatment of Primary Osteosarcoma. Issue 1 (January 2017) - Yodoya, Noriko; Iwamoto, Shotaro; Matsumine, Akihiko; Azuma, Eiichi; Toyoda, Hidemi; Miura, Yoshihiro; Nakatani, Kaname; Imai, Hiroshi; Hirayama, Masahiro; Komada, Yoshihiro
Abstract : Although prognosis in patients with localized osteosarcoma has been dramatically improved by the introduction of multiple chemotherapy agents known as combination chemotherapy, there is growing concern about the development of secondary malignant neoplasms. We report the case of a 13-year-old girl in whom the diagnosis of Ewing sarcoma of bone localized on the shaft of left femur was made 2 years after successful treatment without radiotherapy for osteosarcoma of right proximal femur. EWS-FLI1 fusion gene was detected by reverse transcriptase-polymerase chain reaction. To our knowledge, this is the first case with Ewing sarcoma of the bone as a secondary malignant neoplasm developed in osteosarcoma survivor. We collected 15 cases, included this case, with secondary Ewing sarcoma family of tumor by utilizing the PubMed search and might consider the causes of this secondary cancer.